PENDIDIKAN MULTIKULTURAL MELALUI PEMBELAJARAN BERBASIS LAPANGAN PADA SITUS MATA AIR DI WILAYAH SINGOSARI-LAWANG - Nuzulul Hidayati Marsudi; Aditya Nugroho Widadi; Wahyu Djoko Sulistyo; Nuzulul Hidayati Marsudi; Aditya Nugroho Widadi (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
Indonesia's pluralism does not always have a good impact, this pluralism also poses a threat in the form of the division of the nation. Multicultural education is a solution to prevent the threat of national division. In multicultural education, students will be taught how to respond to the various cultural differences that exist in Indonesia. The history of the spring site in the Singosari-Lawang area holds lessons about how we deal with diversity. Through field-based learning, it is hoped that students can learn and apply lessons from history. In this article the author aims to: 1) explain the history and current function of the spring site in the Singosari-Lawang area, 2) explain the learning carried out at the spring site in the Singosari-Lawang area and 3) explain the main objectives of learning at the spring site in the Singosari-Lawang area.